Can Hypoxia Alter the Anaerobic Capacity Measured by a Single Exhaustive Exercise? - Foresti, Yan Figueiredo; Higino, Wonder Passoni; de Carvalho, Carlos Dellavechia; Esequiel, Guilherme Henrique; Costa, Gabriel Peinado; Bertuzzi, Rômulo; Papoti, Marcelo (International Journal of Sports Medicine, 2023)
The present study aimed to compare the MAODALT in situations of hypoxia and normoxia to confirm the method validity. Seventeen healthy and physically active men participated in this study, aged 25.2±3.2 years. All participants underwent four days of evaluation. The first day was performed a body composition test, an incremental test to exhaustion to determine the maximum oxygen uptake, familiarizing the hypoxia (H) and normoxia (N) situation and the equipment used. On the second, third and fourth days, supramaximal efforts were performed until exhaustion at 110% of maximum oxygen uptake, in a situation of hypoxia (FIO2=14.0%) and normoxia (FIO2=20.9%). The anaerobic capacity was considered the sum of energy supply of the alactic and lactic systens. The absolute or relative anaerobic capacity values were not different (H=3.9±1.1 L, N=3.8±0.9 L, p=0.69), similarly no differences were found for the alactic contribution (H=1.7±0.5 L, N=1.5±0.5 L, p=0.30) and lactic contribution (H=2.3±0.9 L, N=2.3±0.7 L, p=0.85). It can be concluded that the anaerobic capacity measured by a single exhaustive effort is not altered by hypoxia.
Keywords: anaerobic capacity; MAOD; hypoxia; altitude; metabolism